Chronic Kidney Disease, Fluid Overload and Diuretics: A Complicated Triangle - Khan, Yusra Habib (PLoS One, 2016)
BACKGROUND: Despite promising role of diuretics to manage fluid overload among chronic kidney disease (CKD) patients, their use is associated with adverse renal outcomes. Current study aimed to determine the extent of renal deterioration with diuretic therapy. METHODS: A total 312 non-dialysis dependent CKD (NDD-CKD) patients were prospectively followed-up for one year. Fluid overload was assessed via bioimpedance spectroscopy. Estimated GFR (eGFR) was calculated from serum creatinine values by using Chronic Kidney Disease- Epidemiology Collaboration (CKD-EPI) equation. RESULTS: Out of 312 patients, 64 (20.5%) were hypovolemic while euvolemia and hypervolemia were observed in 113 (36.1%) and 135 (43.4%) patients. Overall 144 patients were using diuretics among which 98 (72.6%) were hypervolemic, 35 (30.9%) euvolemic and 11 (17.2%) were hypovolemic. The mean decline in estimated GFR of entire cohort was -2.5 ± 1.4 ml/min/1.73m(2) at the end of follow up. The use of diuretics was significantly associated with decline in eGFR. A total of 36 (11.5%) patients initiated renal replacement therapy (RRT) and need of RRT was more profound among diuretic users. CONCLUSIONS: The use of diuretics was associated with adverse renal outcomes indicated by decline in eGFR and increasing risk of RRT initiation in our cohort of NDD-CKD patients. Therefore, it is cautiously suggested to carefully prescribe diuretics by keeping in view benefit versus harm for each patient.